A comprehensive validation framework addressing utility parameter validation for application in small and medium enterprises (SMEs):A case study in pharmaceutical industry. Issue 1 (31st December 2023) - Subramaniam, Vothia Surian; Prakash, Joshua; Kamaruddin, Shahrul; Khoo, Sze Wei
Abstract: Purpose: The purpose of this paper is to provide a validation framework to guide future validation practitioners towards completing utility validation projects in small and medium enterprise successfully and in shorter duration compared to current practice. Design/methodology/approach: Literature review was carried out on various existing validation frameworks to analyse the positive and negative elements of the frameworks. The identified positive key elements from this analysis were incorporated to develop a comprehensive validation framework that can be used by future validation practitioners to validate utility system in manufacturing companies. Findings: The case study results proved the capability and effectiveness of the new framework as the validation of the reverse osmosis water system was completed successfully with proper documentation and within shorter period compared to previous validation projects in the case study company. Research limitations/implications: The proposed validation framework is well suited for use in small and medium enterprise companies. Further studies should be carried out to ascertain the effect of the framework. Originality/value: This paper provides a comprehensive validation framework that can guide future validation practitioners towards completing validation projects in small and medium enterprise companies successfully and in shorter period.